When Strikes Make Sense and Why: Lessons from Third Republic French Coal Miners - Rojot, Jacques (Relations industrielles / Industrial Relations, 1995)
The article reviews the book, "When Strikes Make Sense and Why: Lessons from Third Republic French Coal Miners," by Samuel Cohn.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Coal industry; History; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Strikes